Iterative Analysis of Dielectric Constant of Patch Antenna Substrate at UHF Band - Kumar Jha, Amish; Gupta, Bharti Gupta; D Swami, Preety (International Journal of Engineering and Technology, 2018)
This paper presents an investigation of effect of substrate material properties on the performance of antenna. The simulations are tested for 30 different dielectric materials on the basic RPA antenna model as well as on the most common U shape model using CST Microwave Studio. Two designs are proposed. On the basis of simulation results it has been concluded that for the first design the best material is which has a dielectric constant of 2.7 (ðœ€r = 2.7) with bandwidth improvements of around 69.33% to 88.6% as compared to the most frequently used materials at present. For the second design the best result is obtained for the material that has dielectric constant in the range 2.0 to 2.7.Â For a material having dielectric constant of 2.1 (ðœ€r = 2.1) bandwidth improvement of around 11.74% with respect to RT Duroid was observed. For the second design, radiations from all other materials were not available in the working frequency range of 1GHz to 6GHz.Â Â